Is a bird in the hand worth two in the future? Intertemporal choice, attachment and theory of mind in school-aged children - Marchetti, Antonella; Castelli, Ilaria; Sanvito, Laura; Massaro, Davide (Frontiers in Psychology, 2014)
Intertemporal choice is a decision-making dilemma related to outcomes of different entity located at different time points. Economic and psychological literature on this topic showed the phenomen of temporal discounting, i.e. the proclivity to devalue the outcome distant in time on the basis of the time delay necessary to obtain it. The goals of this research are to investigate two different components of intertemporal choice separately, namely time and outcome, in school-age children, and the possible link among such components and the security of attachment style and theory of mind. 91 children aged between 6 and 10 years performed two intertemporal choice tasks, first and second order false belief tasks and the Separation Anxiety Task in the Family and School versions. Results showed that the two components of intertemporal choice (waiting tolerance and sensitivity to delayed outcome) are stately interrelated ; the quality of the attachment to the family caregiver affects the tolerance to waiting time and first order false belief understanding affects both the components of intertemporal choice.